2021
DOI: 10.1093/ajhp/zxab152
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model to predict and manage drug shortages

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
5
1
1
Order By: Relevance
“…Seven predictors were included in the nomogram: volume-based procurement, therapeutic class, drug dosage form, distribution firm, take orders, order date, and unit price. Among them, drug dosage forms and therapeutic classes are consistent with previous reports [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Seven predictors were included in the nomogram: volume-based procurement, therapeutic class, drug dosage form, distribution firm, take orders, order date, and unit price. Among them, drug dosage forms and therapeutic classes are consistent with previous reports [24].…”
Section: Discussionsupporting
confidence: 91%
“…The study also found no statistical significance in the probability of shortage for both Chinese and foreign-funded drugs. This is inconsistent with some literature reports [24]. The reason may be that the national conditions of each country are different or the…”
Section: Plos Onecontrasting
confidence: 72%
See 1 more Smart Citation
“…A few publications studied the costs of specific shortages but excluded personnel costs [ 45 – 47 ]. For our framework, costs can be based on historical costs, actual costs as well as forecasting costs using financial or economic modelling [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Junto al procesamiento masivo de datos se han usado diferentes algoritmos con el objeto de encontrar modelos que describan el comportamiento de la demanda (Gunasekaran et al, 2017). Se han usado algoritmos de Máquinas de Soporte Vectorial (Ahmed y Farzana, 2020), y algoritmos de regresión lineal o series de tiempo (Liu, et al, 2021;Miller, et al, 2020;Zhou, et al, 2019, Pavlyshenko, 2019, que utilizan métodos de analítica de datos y brindan apoyo para decidir los niveles de inventario.…”
unclassified